Faktor-Faktor yang Berhubungan dengan Perilaku Konsumsi Tablet Tambah Darah Pada Ibu Hamil: Factors Related to The Behavior of Consuming Blood-Added Tablets in Pregnant Women - Elsha Palupi, Elsha Palupi; Ayu, Ira Marti; Heryana, Ade; Mustikawati, Intan Silviana (Poltekes Kemenkes Tanjungpinang, 2023)
Anemia is a health problem in pregnant women. Globally, there was 36,5% anemia in pregnant women (2019). Giving blood-added tablets is one of the important efforts to prevent and control anemia due to iron deficiency. Preliminary studies showed that 5 out of 15 pregnant women did not comply to consumed blood-added tablets (33.3%). The study objective was to determine the factors related to the behaviour of consuming blood-added tablets in third pregnant women at RSIA Avisena in 2022. This study has an 84 sample size and purposive sampling techniques. This study used a cross-sectional study design. The consumption of blood-added tablets is a dependent variable. The knowledge, attitudes, side effects, and husband support are independent variables. Collection data used primary data with questionnaires. Data is analyzed with bivariate analysis (the Chi-Square test). There was a relationship between knowledge (PR=3.32; 95%CI=2.03- 5.43) and there was no relationship between attitudes (PR=1.42; 95%CI=0.80-2.51) side effects (PR=1.21; 95%CI=0.78-1.88), husband support (PR=1.28; 95%CI=0.83-1.97). Hospitals should provide a leaflet explaining the tablet to increase pregnant women's knowledge. The hospital can also utilize WhatsApp groups to educate them about the benefits of Fe tablets and remind them to comply with taking Fe tablets.